Peran Inovatif Fintech dan ChatGPT di Dunia Pendidikan - rizky_amnah, Rizky; Nurfaisah, Nurfaisah; Tanjung , Elapinia; Gautama, Budi (Fakultas Ekonomi dan Bisnis Islam, 2024)
The digital era has transformed various aspects of life, including education. The presence of Artificial Intelligence (AI) has impacted various fields of life. One AI product is ChatGPT, developed by the nonprofit company OpenAI, which was founded in 2015.ChatGPT, an innovative AI tool, has emerged as an alternative learning resource for addressing educational challenges. ChatGPT by OpenAI is a machine-based artificial intelligence technology trained to mimic human conversation through Natural Language Processing (NLP). In practice, ChatGPT can be utilized to generate scientific writing or even books, guided by well-constructed prompts that enhance its effectiveness. This opens up vast opportunities for innovation in Indonesian education, particularly in improving students' writing skills in schools and universities. This approach helps students achieve the six key competencies required in Education 4.0: critical thinking, collaboration, communication, creativity, character education, and citizenship. An experiment using ChatGPT showed that it could generate a 693-word piece, which can be further developed for subsequent assignments, providing valuable assistance to students in their educational journey.